The efficacy and safety of mirabegron compared with solifenacin in overactive bladder patients dissatisfied with previous antimuscarinic treatment due to lack of efficacy: results of a noninferiority, randomized, phase IIIb trial - Jose E. Batista; Heinz Kölbl; Sender Herschorn; Tomasz Rechberger; Javier Cambronero; Michael Halaska; Alex Coppell; Mathilde Kaper; Moses Huang; Emad Siddiqui (Therapeutic Advances in Urology, 2015)
Objective: To compare the efficacy and safety of mirabegron 50 mg and solifenacin 5 mg in overactive bladder (OAB) patients dissatisfied with previous antimuscarinic treatment due to lack of efficacy. Patients and methods: This randomized, double-blind, phase IIIb, noninferiority study, enrolled male and female patients aged ⩾18 years old, with symptoms of OAB for ⩾3 months, who were dissatisfied with their previous antimuscarinic drug due to lack of efficacy. A total of 1887 patients were randomized to receive mirabegron 50 mg ( n = 943) or solifenacin 5 mg ( n = 944) daily for 12 weeks. The primary efficacy endpoint was change from baseline to end of treatment in mean number of micturitions/24 h. Noninferiority was confirmed if the lower limit of the two-sided 95% confidence interval (CI) for the treatment difference between solifenacin and mirabegron was > −0.20. Secondary efficacy endpoints, which included change from baseline in mean number of incontinence episodes/24 h, urgency incontinence episodes/24 h, urgency episodes (grade 3 or 4)/24 h and nocturia episodes/24 h, were analyzed using analysis of covariance. Results: For the primary endpoint, adjusted mean treatment difference (95% CI) in mean number of micturitions/24 h was −0.18 (−0.42, 0.06) and therefore noninferiority of mirabegron to solifenacin was not demonstrated. Both treatments demonstrated clinically meaningful reductions in efficacy variables and were well tolerated, with a lower incidence of dry mouth with mirabegron. Conclusions: Noninferiority of mirabegron compared with solifenacin for reduction in micturition frequency could not be demonstrated in this population of OAB patients who were dissatisfied with previous antimuscarinic therapy due to lack of efficacy. Both mirabegron and solifenacin improved key OAB symptoms with no statistically significant differences observed between the two treatments. Both drugs were well tolerated.